Investigating sweep efficiency improvement in oil-wet porous media by the application of functionalized nanoparticles. (1st May 2020) - Maaref, Sepideh; Kantzas, Apostolos; Bryant, Steven
Abstract: Nanoparticle stabilized emulsions have gained recent attention as mobility control agents in EOR processes. Some recent studies have shown in-situ formation of nanoparticle stabilized emulsions during displacement of a brine phase containing nanoparticles by another non-wetting phase such as n-octane under water-wet conditions. The objective of this research is to evaluate the hypothesis of nanoparticle stabilized emulsion formation by varying the system wettability toward oil-wet condition. Partially hydrophobic silica NPs with proper interface affinity are firstly synthesized and characterized in this study. A series of drainage displacement experiments are then conducted in the oil-wet sandpack embedded in a CT scanner, in the absence or presence of the functionalized NPs and a surfactant. CT-scans during waterflooding in the presence of NPs and surfactant has revealed a piston like displacement as a result of in-situ emulsion formation at the water invading front, which is associated with later water breakthrough, higher pressure drop, considerable pressure fluctuations, and higher oil recovery compared to the control experiment. The effect of nanofluid slug size and nanofluid viscosity is further investigated on sweep efficiency improvement during drainage displacement. The results have revealed that the presence of an oil-based nanofluid is effective in re-distributing the preferential water flow paths into a more stable front as a result of in-situ emulsification and the overall displacement efficiency depends on the nanofluid propagation in porous media. The oil-based nanofluid flooding followed by waterflooding utilized here is found to be a potential conformance control technique for oil recovery in oil-wet porous media.